Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1080/13102818.2005.10817283
|View full text |Cite
|
Sign up to set email alerts
|

Sharka Disease in Bulgaria: Past, Present and Future

Abstract: This review is an attempt to synthesize almost 70 years investigations of Sharka disease in Bulgaria. The results obtained from first virus discovery, disease dissemination throughout stone fruit growing regions, present virus incidence on different Prunus species, natural hosts of the virus, virus detection, strain characterization, susceptibility of plum, peach and apricot cultivars to Sharka disease and virus control measures applied in the past and today are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Milosevic et al reported about 50% fruit drop of ‘Čačanska rodna’ infected trees. Even higher (80–100%) fruit drop was observed in ‘Kyustendilska sinja sliva’ . Much higher fruit drop was observed in a long‐time infected tree than in a short‐time infected tree.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Milosevic et al reported about 50% fruit drop of ‘Čačanska rodna’ infected trees. Even higher (80–100%) fruit drop was observed in ‘Kyustendilska sinja sliva’ . Much higher fruit drop was observed in a long‐time infected tree than in a short‐time infected tree.…”
Section: Discussionmentioning
confidence: 92%
“…Even higher (80-100%) fruit drop was observed in 'Kyustendilska sinja sliva'. 8 Much higher fruit drop was observed in a long-time infected tree than in a short-time infected tree. Based on this finding, it can be concluded that fruit drop increases with duration of infection.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Similar results were obtained with samples collected from plum 'Katinka' growing in the same garden. 'Katinka' is considered to be resistant by its breeders (Hartman, 1999), but has shown to be very susceptible to PPV-M by Kamenova and Milusheva (2005). In Maribor, PPV could be detected only in stalks using real time PCR (Table 2), but the Ct value was very low indicating a low concentration of the virus.…”
Section: Resultsmentioning
confidence: 99%